[The Demand for Money: A Cross-Section Study of Business Firms"]: Reply - Meltzer, Allan H. (Quarterly Journal of Economics, 1965)
This essay provides the kind of concise and incisive survey that we have learned to await with anticipation from the ever-active pen of Professor Johnson. This time he is discussing the role of monetary policy as a stabilization device. The paper, originally prepared for the Canadian Royal Commission on Banking and Finance, deals mainly with Canadian problems. But the author ranges over the pros and cons of a number of issues of general interest, and there are useful comments on a variety of open questions.